Order-Unit Spaces which are Banach Dual Spaces - Berdikulov, M. A. (Журнал математичної фізики, аналізу, геометрії, 2006)
Spaces of selfadjoint elements of a C*-algebra or a von Neumann algebra, and also JB- and JBW-algebras are examples of order-unit spaces. A von Neumann algebra and a JBW-algebra possess predual spaces, but, generally speaking, a JB-algebra and a C*-algebra don’t have this property. In this work, conditions are found for an order-unit space to possess a predual space. Moreover, a condition is obtained characterizing JBW-algebras among order-unit spaces having a predual space.Mathematics Subject Classification: 46B40, 46L50, 46G12, 46B10.